The Influence of the TGT (Teams Game Tournament) Method on Student Motivation and Learning Outcomes - Muhammad Hamam (Publikasi Indonesia, 2026)
Low student motivation and learning outcomes remain a persistent challenge in science education, particularly when conventional teaching methods such as lectures dominate classroom practices. This study aims to determine the influence of the application of the Teams Game Tournament (TGT) learning method in an effort to increase student motivation and learning outcomes in the food chain material of science subjects. This research is a Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subject of the study is 21 students of class VII A MTSN 9 Indramayu. The data collection technique used observation, tests, and learning motivation questionnaires. The results showed that the application of the TGT method could increase students' overall learning motivation from 59.3% (Medium category) in cycle I to 77.0% (High category) in cycle II. Intrinsic motivation increased from 59.0% to 75.0%, extrinsic motivation from 59.0% to 78.0%, and situational motivation from 60.0% to 78.0%. Student learning outcomes also increased from an average score of 45.0 in the first cycle to 68.4 in the second cycle (an increase of 23.4 points or 52.0%). The percentage of learning completeness increased from 31.8% in the first cycle to 77.3% in the second cycle. Student activity increased from 40.9% in cycle I to 100% in cycle II. This study proves that the TGT method is effective in increasing student motivation and learning outcomes in science learning food chain materials.